Determination Of Delivery Routes For Food Materials At Healthy Food Brand Outlets In Bandung City Using Nearest Neighbor And Nearest Insertion Methods - Yulianto, Irwan; Martikasari, Arida Murti (Journal of Engineering Science and Technology Management, 2025)
Efficient distribution is a critical factor in the food sales industry to ensure product quality, cost effectiveness, and customer satisfaction. The reliance on third-party online delivery services for distributing raw food ingredients has created significant logistics costs for a healthy food company in Bandung. To address this issue, the company aims to manage its own logistics using available delivery vehicles. The main challenge lies in determining the optimal delivery route that minimizes time and cost while serving an increasing number of outlets. This study applies a constructive heuristic approach to the Vehicle Routing Problem (VRP), since no prior research has examined delivery routes for this company. Constructive heuristics are chosen for their ability to provide feasible solutions that are easy and quick to implement. Two methods are employed: the Nearest Neighbor and the Nearest Insertion. The results indicate that the Nearest Neighbor method produces a total distance of 70.3 km, while the Nearest Insertion yields 68.1 km. Thus, the Nearest Insertion method achieves a shorter route by 2.2 km, equivalent to a 3.1% reduction compared with Nearest Neighbor. Based on these findings, the Nearest Insertion method is selected as the optimal route. This research provides a practical initial framework for improving logistics efficiency in food distribution and can serve as a foundation for future optimization studies.